Balancing Interests in Responding Pandemic Covid-19 in Palembang: The Policy Networks Analysis - Eti Yusnita; Siti Anisyah (Jurnal Studi Sosial dan Politik, 2023)
This research examines the political economy of policies and policy networks in Palembang policies to handle pandemic. So far, policy studies with a political nature have always placed policy products as the result of the compromise based on "profit and loss" between stakeholders. Therefore, policy products always prioritize rationality. The significance of our research is trying to analyze rational and non-rational factors in policy studies with a political character. Our research focus is pandemic policy in Palembang City. We use a political economy approach to analyze policy network which assumes that every policy always involves networks -state and non-state - having an interest in the policy. The method we use is a case study-based qualitative method with a data collection strategy through in-depth interviews for primary data and documentation studies to collect secondary data. The study found that the character of policy network for dealing the pandemic in Palembang was a bureaucratic network in which the stakeholders were dominated by the bureaucracy. Then, we also find that in policy studies in crisis situations, the "humanity" factor appears as the interests of the stakeholders, who generally prioritize the factor of rationality.